Bloomsbury women & the wild colonial girl - Parry, Lorae (Women's Play Press, 2010)
"The play focuses on Katherine Mansfield's friendships and relationships with women, in particular her relationship with Virginia Woolf and her ongoing friendship with Ida Baker (LM). It is compiled entirely from the words of Katherine Mansfield, Ida Baker, Virginia Woolf and other members of The Bloomsbury Group."--Publisher's description.